406 A 50 years old man with a late presentation of arrhythmogenic cardiomyopathy. (8th December 2021) - Dellino, Carlo Maria; Bariani, Riccardo; Cipriani, Alberto; Marra, Martina Perazzolo; Pilichou, Kalliopi; Iliceto, Sabino; Corrado, Domenico; Basso, Cristina; Rigato, Ilaria; Bauce, Barbara
Abstract: In January 2014 a 50 years old man without previous medical history experienced a syncopal episode. During evaluation at Emergency department (ED) a sustained ventricular tachycardia (VT) with haemodynamic compromise was found and successfully treated with DC shock. The patient was admitted to the Coronary Care Unit (CCU) where the ECG showed diffuse low QRS voltages and flattened T waves. Coronary angiography showed normal coronary arteries. 2-D echocardiogram documented the presence of a mildly dilated left ventricle (LV) with a mildly decreased systolic function (EF : 41%); the right ventricle (RV) was severely dilated (REDV : 41 cmq/mq) with a severe systolic dysfunction (fractional area change: 21%) with diffuse hypokinesia and akinesia of subtricuspid region. Cardiac magnetic resonance (CMR) confirmed ventricular dimensional and kinetic abnormalities and tissue characterization sequences demonstrated the presence of fatty infiltration of the epicardial segments of LV lateral wall and of RV free wall. After gadolinium injection, late gadolinium enhancement (LGE) presented the same distribution of the fatty infiltration. A diagnosis of arrhythmogenic cardiomyopathy (AC) was made and ICD in secondary prevention was implanted. The patient was treated with Sotalol (240 mg/daily) and remained asymptomatic and free from sustained ventricular arrhythmias for five years. In January 2019 he started to complain asthenia, dyspnoea (NYHA II) and anorexia and he was admitted to ED where a persistent slow VT was detected. Echocardiogram showed a severely dilated LV with severe systolic dysfunction (EF: 30%) with substantially unchanged RV features. One year later he experienced an heart failure (HF) episode with further reduction of LV systolic function (EF: 21%). Cardiopulmonary test documented a severe ventilation/perfusion mismatch (VE/VCO2 slope 50.6) and severe reduction of the exercise tolerance (VO2 peak 9.2 ml/kg/min). In March 2021 the patient started heart transplantation check list. Three weeks after the discharge he was transplanted. In conclusion, this clinical case highlights an infrequent late presentation of AC, with an initial high arrhythmic burden and a following rapid progression to refractory HF requiring heart transplantation.